Periodic limb movements in tetraplegia. (4th May 2018) - Peters, Annemieke Emma Josina; van Silfhout, Lysanne; Graco, Marnie; Schembri, Rachel; Thijssen, Dick; Berlowitz, David J.
Abstract : Objective : To establish the prevalence of Periodic Limb Movements during Sleep (PLMS) in patients with tetraplegia, controlling for obstructive sleep apnea. To explore whether demographic and injury characteristics affect PLMS. Study Design : Retrospective cohorts. Setting and Participants : One hundred seventy-three participants with acute (<12 months) and 92 with chronic (>12 months) tetraplegia who underwent full overnight diagnostic sleep studies. Interventions and outcome measures : Two hundred sixty-two sleep study recordings were included. A randomly selected subgroup of 21 studies was assessed for PLM during wakefulness. Data were analysed according to the current American Academy of Sleep Medicine guidelines. Results : Of the participants, 41.6% (43(15.7) years and 14.9% female) had a motor and sensory complete lesion. Sleep was poor with both OSA (87.8% with apnea hypopnoea index ≥ 5) and PLMS (58.4% with PLMS per hour PLMSI > 15) highly prevalent. There was no difference in the PLMSI between those with OSA (36.3(39.8)) or without (42.2(37.7), P = 0.42). PLMS were evident during REM and NREM sleep in all of the 153 patients with PLMSI > 15. All 21 participants in the subgroup of studies analysed for the PLM during quiet wakefulness, exhibited limb movements. None of the modelled variables (injury completeness, gender, OSA severity or time since injury) significantly predicted a PLMSI > 15 (P = 0.343). Conclusion : In conclusion, this study confirms the high prevalence of PLM in tetraplegia and the presence of leg movements in NREM and REM sleep along with wakefulness after controlling for OSA. No associations between the presence of PLMS and patient characteristics or injury specific aspects were found.